Anthracimycin Activity Against Contemporary Methicillin-Resistant Staphylococcus aureus - Hensler, Mary E. (2014)
Anthracimycin is a recently discovered novel marine-derived compound with activity against Bacillus anthracis. We tested anthracimycin against an expanded panel of Staphylococcus aureus strains in vitro and in vivo. All strains of S. aureus tested, including methicillin-sensitive (MSSA), methicillin-resistant (MRSA), and vancomycin-resistant strains of S. aureus were sensitive to anthracimycin at minimum inhibitory concentrations (MIC) of < 0.25 mg/L. Although its post-antibiotic effects were minimal, anthracimycin exhibited potent and rapid bactericidal activity, with a > 4-log kill of USA300 MRSA within 3 hours at 5 times its MIC. At concentrations significantly below the MIC, anthracimycin slowed MRSA growth and potentiated the bactericidal activity of the human cathelicidin, LL-37. The bactericidal activity of anthracimycin was somewhat mitigated in the presence of 20% human serum, and the compound was minimally toxic to human cells, with an IC(50) = 70 mg/L against human carcinoma cells. At concentrations near the MIC anthracimycin inhibited S. aureus nucleic acid synthesis as determined by optimized macromolecular synthesis methodology, with inhibition of DNA and RNA synthesis occurring in the absence of DNA intercalation. Anthracimycin at a single dose of 1 or 10 mg/kg was able to protect mice from MRSA-induced mortality in a murine peritonitis model of infection. Anthracimycin provides an interesting new scaffold for future development of a novel MRSA antibiotic.